The Most Effective Drugs in the Treatment of Myocarditis Disease - Nozimjon o’g’li, Salomov Shoxabbos; Makhmudovich, Aliev Husniddin (Indonesian Journal Publisher, 2024)
Myocarditis, characterized by inflammation of the heart muscle, presents a complex and challenging clinical scenario. This review explores the landscape of pharmacological interventions in the treatment of myocarditis, aiming to identify the most effective drugs in managing this inflammatory cardiac condition. A comprehensive analysis of current literature encompasses clinical trials, observational studies, and experimental models to evaluate the efficacy of various drug classes. From immunosuppressive agents to anti-inflammatory medications, the review delineates the mechanisms of action, safety profiles, and clinical outcomes associated with different drug interventions. The synthesis of evidence provides valuable insights into the pharmacotherapeutic strategies that demonstrate the highest efficacy in mitigating inflammation, preserving cardiac function, and improving patient outcomes in myocarditis